2021
DOI: 10.1186/s12879-021-06222-4
|View full text |Cite
|
Sign up to set email alerts
|

Modes of transmission of SARS-CoV-2 and evidence for preventive behavioral interventions

Abstract: COVID-19 is a novel disease caused by SARS-CoV-2. During the global vaccination rollout, it is vital to thoroughly understand the modes of transmission of the virus in order to prevent further spread of variants and ultimately to end the pandemic. The current literature suggests that SARS-CoV-2 is transmitted among the human population primarily through respiratory droplets and, to a lesser extent, via aerosols. Transmission appears to be affected by temperature, humidity, precipitation, air currents, pH, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 82 publications
0
94
0
8
Order By: Relevance
“…Transmission of SARS-CoV-2 may occur via several biologically plausible routes and depends on multiple factors, including the infectious dose (or inoculum), virus viability, exposure distance and duration, environmental factors (temperature, humidity, precipitation, pH, airflow/ventilation, solar ultraviolet radiation, chemicals), and host factors (breathing rate, respiratory tract morphology, target tissues, receptor distribution, host barriers and immune responses) [49,[254][255][256]. Transmission risk in specific settings is further influenced by existing infection prevention and control (IPC) practices and public health interventions [257,258].…”
Section: The Modes Of Transmission Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission of SARS-CoV-2 may occur via several biologically plausible routes and depends on multiple factors, including the infectious dose (or inoculum), virus viability, exposure distance and duration, environmental factors (temperature, humidity, precipitation, pH, airflow/ventilation, solar ultraviolet radiation, chemicals), and host factors (breathing rate, respiratory tract morphology, target tissues, receptor distribution, host barriers and immune responses) [49,[254][255][256]. Transmission risk in specific settings is further influenced by existing infection prevention and control (IPC) practices and public health interventions [257,258].…”
Section: The Modes Of Transmission Of Sars-cov-2mentioning
confidence: 99%
“…Unfortunately, such studies under controlled laboratory conditions do not reflect physiological host processes and real-world environmental conditions related to viral transmission [270,337]. Respiratory particle transmission and viability over long distances are subject to changes in ambient temperature, relative humidity, airflow/ventilation, solar ultraviolet radiation (sunlight), and chemicals leading to evaporation, supersaturation, dilution, or inactivation [49,[254][255][256]. Aerosol transmission, direct contact transmission, and fomite transmission have been experimentally demonstrated in multiple animal models [49,[338][339][340][341][342][343].…”
Section: Laboratory Studies and Modeling Datamentioning
confidence: 99%
“…Additionally, in clinical trials, all three vaccines induce robust T-cell immunity and significantly reduced the rate of symptomatic coronavirus disease 2019 (COVID-19) (4-6). SARS-CoV-2 is an aerosol transmissible virus, which upon inhalation into the mucosa of the nasopharynx and oral cavity, infects locally and disseminates systemically, progressing into pulmonary and multi-organ infection (7)(8)(9). The human nasal and oral epithelium have been shown to highly express SARS-CoV-2 entry factors in vitro (10)(11)(12) and studies using animal models have shown the ability of SARS-CoV-2 to infect and replicate in the olfactory epithelium of the nasal turbinates in mice (13,14), hamsters (15)(16)(17)(18) and rhesus macaques (7).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 is an aerosol transmissible virus, which upon inhalation into the mucosa of the nasopharynx and oral cavity, infects locally and disseminates systemically, progressing into pulmonary and multi-organ infection (7)(8)(9). The human nasal and oral epithelium have been shown to highly express SARS-CoV-2 entry factors in vitro (10)(11)(12) and studies using animal models have shown the ability of SARS-CoV-2 to infect and replicate in the olfactory epithelium of the nasal turbinates in mice (13,14), hamsters (15)(16)(17)(18) and rhesus macaques (7). Consequently, both infection and transmission of infection occur via the oral-pharyngeal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 disease is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel beta-coronavirus that is primarily transmitted via respiratory droplets and aerosols with a likely more limited transmission risk via fomites [1][2][3]. After the first reports of the disease in December 2019, 120 million infections and 2.5 million deaths were reported worldwide by the World Health Organization (WHO) during the first year of the pandemic [1].…”
Section: Introductionmentioning
confidence: 99%